Network companies, land grabbing, and financialization in South America. Issue 3 (3rd April 2021) - Sosa Varrotti, Andrea P.; Gras, Carla
ABSTRACT: This paper examines the connections between two global phenomena: land grabbing and financialization of farmland and agriculture. Drawing upon case studies, we analyse the expansion of two large-scale agricultural firms founded in Argentina to the Latin American Southern Cone during the 2000s commodities boom, focusing on their network models and business strategies. Based on a qualitative approach towards financial and productive practices, we unravel some intersections between the financialization of farmland, land grabs, and renewed social relations and patterns of agricultural organization. We propose that financial and productive logics impinge upon each other and that this imbrication entails tensions and contradictions in crucial but differentiated ways.